2005
DOI: 10.1371/journal.pmed.0020263
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression in Dorsolateral Prefrontal Cortex of CAPON in Schizophrenia and Bipolar Disorder

Abstract: BackgroundWe have previously reported linkage of markers on chromosome 1q22 to schizophrenia, a finding supported by several independent studies. Within this linkage region, we have identified significant linkage disequilibrium between schizophrenia and markers within the gene for carboxyl-terminal PDZ ligand of neuronal nitric oxide synthase (CAPON). Prior sequencing of the ten exons of CAPON failed to reveal a coding mutation associated with illness.Methods and FindingsWe screened a human fetal brain cDNA li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 30 publications
7
94
1
5
Order By: Relevance
“…The higher bands (Ϸ70 kDa) could reflect either posttranslational modification of CAPON or nonspecific crossreactivity. Notably, the ventricular myocardium also displayed a band Ϸ30 kDa in size detected by antibody against the C terminus of CAPON, but not by antibody against an N-terminal epitope, which is consistent with the short-form of CAPON (13). Immunofluorescent staining of freshly isolated ventricular myocytes revealed a cytoplasmic distribution pattern of the soluble CAPON protein with focal accentuation over the perinuclear region and the sarcolemmal membrane (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The higher bands (Ϸ70 kDa) could reflect either posttranslational modification of CAPON or nonspecific crossreactivity. Notably, the ventricular myocardium also displayed a band Ϸ30 kDa in size detected by antibody against the C terminus of CAPON, but not by antibody against an N-terminal epitope, which is consistent with the short-form of CAPON (13). Immunofluorescent staining of freshly isolated ventricular myocytes revealed a cytoplasmic distribution pattern of the soluble CAPON protein with focal accentuation over the perinuclear region and the sarcolemmal membrane (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…The full-length transcript encompassing 10 exons contains both PTB-and PDZ-binding domains, whereas the C-terminal transcript containing the last 2 exons encodes only the PDZ-binding domain (13). We found that both full-length and short CAPON isoforms are expressed in guinea pig ventricular myocytes using the same CAPON antibody (13) predicted to react with the C terminus of CAPON. The full-length isoform comigrated at the same level as a brain-enriched protein band and a band from HEK293 cells expressing CAPON.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Blocking the PDZ-domain of NOS-I with small molecule inhibitors has been suggested as a possible therapeutic approach in the treatment of depression, a hypothesis that is supported by preclinical evidence (Doucet et al, 2013). Since we show that expression levels of NOS-I are reduced in rs41279104 risk allele carriers, and since elevated expression of NOS1AP interfering with post-synaptic targeting of NOS-I (Jaffrey et al, 2002;Jaffrey et al, 1998) is elevated in schizophrenic patients (Xu et al, 2005), a comparable approach (i.e., blocking NOS-I -NOS1AP interaction with small molecules) might provide a feasible strategy for treatment at least in patients carrying this risk allele. In this context, it is also interesting to note that another SNP that was associated with schizophrenia in a family-based study (and therefore not included in our meta-analysis) produced elevated NOS1AP promoter activity in human cell lines ).…”
Section: ) the Binding Of Nos1ap To Nos-i Directly Competes Withmentioning
confidence: 79%
“…The original isoform CAPON (Jaffrey et al, 1998) has also been termed NOS1AP or NOS1AP-L (Carrel et al, 2009). As well, a short isoform containing the last two exons of the NOS1AP gene with a unique 5Ј sequence is known as NOS1AP-S (Xu et al, 2005). Since our isoform is longer than the originally identified NOS1AP/CAPON/NOS1AP-L isoform, and since it is the third isoform to be described, we have called it NOS1APc.…”
Section: Scrib Also Associates With a Novel Nos1ap Isoformmentioning
confidence: 95%